A Bioinspired System for Light‐Driven Water Oxidation with a Porphyrin Sensitizer and a Tetrametallic Molecular Catalyst. Issue 21 (8th April 2015) - Natali, Mirco; Deponti, Elisa; Vilona, Debora; Sartorel, Andrea; Bonchio, Marcella; Scandola, Franco
Abstract: Inspired by natural photosynthesis, the aim of light‐driven water splitting is to produce renewable fuels by exploiting solar radiation. Sustained hydrogen production is desirable in such systems, and the oxidation of water to oxygen is currently recognized as the bottleneck of the entire process. Therefore, solutions for this difficult task retain a fundamental interest. In this paper, we present a bioinspired, three‐component system for water oxidation that comprises a tetracationic porphyrin Zn II complex as the photosensitizer, a tetraruthenium water‐oxidation catalyst, and sodium persulfate as the electron acceptor. An in‐depth photophysical study reveals the photogeneration of a pentacation radical of the porphyrin (quantum yield up to Φ = 1.01) upon oxidative quenching of the triplet excited state by persulfate. Electron transfer from the water‐oxidation catalyst to the pentacation radical (hole scavenging) is slow (bimolecular rate constant, k < 4 × 10 7 M –1 s –1 ), and this is likely the main reason for the low efficiency of the system in photocatalytic tests for water oxidation. Perspectives for improvements of the system and for the development of a light‐activated device for water splitting are discussed. Abstract : The photoinduced events and the light‐driven water‐oxidation ability of a bioinspired, three‐component catalyst/photosensitizer/acceptor molecular system are investigated.